The role of simulation in intertemporal choices - O'Connell, Garret; Christakou, Anastasia; Chakrabarti, Bhismadev (Frontiers in Neuroscience, 2015)
One route to understanding the thoughts and feelings of others is by mentally putting one’s self in their shoes and seeing the world from their perspective, called simulation. Simulation is potentially used not only for inferring how others feel, but also for predicting how we ourselves will feel in the future. For instance, one might judge the worth of a future reward by simulating how much it will eventually be enjoyed. In intertemporal choices between smaller immediate and larger delayed rewards, it is observed that as the length of delay increases, delayed larger rewards lose subjective value; a phenomenon known as temporal discounting. In this article, we develop a theoretical framework for the proposition that simulation mechanisms involved in empathising with others also underlie intertemporal choices. This framework yields a testable psychological account of temporal discounting based on simulation. Such an account, if experimentally validated, could have important implications for how simulation mechanisms are investigated, and makes predictions about special populations characterised by putative deficits in simulating others.